A 28-day Gavage Toxicity Study in Fischer 344 Rats with 3-methylfuran. (February 2015) - Gill, Santokh; Kavanagh, Meghan; Cherry, Wendy; Barker, Michael; Weld, Madeline; Cooke, Gerard M.
3-Methylfuran is produced in foods during food processing and preservation techniques that involve heat treatment such as cooking, jarring, canning, and pasteurization. Currently, there are no studies available on the toxicity of 3-methylfuran. We conducted a 28-day gavage toxicity study (7 days per week) using doses of 0.0, 0.1, 0.3, 1.5, 3.0, 6.0, 12.0, and 25.0 mg/kg bw/day in order to determine the dose range needed to establish a no observed adverse effect level and to better characterize nonneoplastic effects including those affecting hematology, clinical biochemistry, gross morphology, and histopathology. Histological changes of the liver were noted in all treated animals and gross changes were noted beginning at 3.0 mg/kg bw/kg. Alterations in the activity of serum enzymes indicative of effects on the liver were observed, including increases in levels of alanine transaminase and alkaline phosphatase at the highest dose. There was a significant increase in serum thyroxine (T4) and triiodothyronine (T3), which was not accompanied by histological changes in the thyroid. For the most part, statistically significant changes were seen only at the highest dose for hematology and at the 2 highest doses for clinical chemistry parameters. In contrast, mild histological lesions in the liver were observed even at the lowest dose of 0.1 mg/kg bw/day.